2020
DOI: 10.1002/evan.21854
|View full text |Cite
|
Sign up to set email alerts
|

Issues of theory and method in the analysis of Paleolithic mortuary behavior: A view from Shanidar Cave

Abstract: Mortuary behavior (activities concerning dead conspecifics) is one of many traits that were previously widely considered to have been uniquely human, but on which perspectives have changed markedly in recent years. Theoretical approaches to hominin mortuary activity and its evolution have undergone major revision, and advances in diverse archeological and paleoanthropological methods have brought new ways of identifying behaviors such as intentional burial. Despite these advances, debates concerning the nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 99 publications
(233 reference statements)
0
10
0
2
Order By: Relevance
“…The presence of Neanderthals in the Zagros has been known for decades [ 26 , 27 , 29 , 32 ]. However, few sites (Shanidar, Warwasi, Ghar-e-Khar, Kaldar, Ghamari, Gilvaran) preserve both MP and UP industries [ 25 – 27 , 51 , 52 ], while chronometric ages derive only from the old and new excavations at Shanidar, which point to the use of the cave by Neanderthals between 70,000 and 45,000 BP [ 26 – 28 ]. The age between 43,000 and 41,000 cal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of Neanderthals in the Zagros has been known for decades [ 26 , 27 , 29 , 32 ]. However, few sites (Shanidar, Warwasi, Ghar-e-Khar, Kaldar, Ghamari, Gilvaran) preserve both MP and UP industries [ 25 – 27 , 51 , 52 ], while chronometric ages derive only from the old and new excavations at Shanidar, which point to the use of the cave by Neanderthals between 70,000 and 45,000 BP [ 26 – 28 ]. The age between 43,000 and 41,000 cal.…”
Section: Discussionmentioning
confidence: 99%
“…MP sites are relatively numerous, although only three have yielded Neanderthal fossils. The best-known of these is Shanidar, where the remains of ten Neanderthals were discovered [ 26 – 28 ]. The Shanidar Neanderthals have played a major role in the discussions about the complexity of Neanderthal behaviour, both for the presence of older-aged individuals in the fossil assemblage and the controversial claims of a ‘flower burial’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multidisciplinary approach should also be extended to other Neandertal skeletons and sites, to provide robust data that will allow us to contextualize information at both the site and regional scale. This is necessary to seriously address historically debated issues such as the relationship of Neandertals with the Châtelperronian industry and the chronological and geographical extent of funerary behaviours 60 , as well as providing a more precise chronology for the last Neandertals.…”
Section: Mpi-codementioning
confidence: 99%
“…Archeological studies have shown evidence of caves being used by man since the Paleolithic period. Mainly, but not exclusively for shelter and storage, but also as places for artistic expression, burial, or ceremonial sites [1,2]. Today, caves are mainly objects of tourist activity, with people visiting show caves to admire Paleolithic paintings or interesting rock formations [3,4].…”
Section: Introductionmentioning
confidence: 99%